Improved Stability of Rifampicin in the Presence of Gastric-Resistant Isoniazid Microspheres in Acidic Media - Chiluba Mwila; Roderick B. Walker (MDPI AG, 2020)
The degradation of rifampicin (RIF) in an acidic medium to form 3-formyl rifamycin SV, a poorly absorbed compound, is accelerated in the presence of isoniazid, contributing to the poor bioavailability of rifampicin. This manuscript presents a novel approach in which isoniazid is formulated into gastric-resistant sustained-release microspheres and RIF into microporous floating sustained-release microspheres to reduce the potential for interaction between RIF and isoniazid (INH) in an acidic environment. Hydroxypropyl methylcellulose acetate succinate and Eudragit® L100 polymers were used for the manufacture of isoniazid-loaded gastric-resistant sustained-release microspheres using an o/o solvent emulsification evaporation approach. Microporous floating sustained-release microspheres for the delivery of rifampicin in the stomach were manufactured using emulsification and a diffusion/evaporation process. The design of experiments was used to evaluate the impact of input variables on predefined responses or quality attributes of the microspheres. The percent degradation of rifampicin following 12 h dissolution testing in 0.1 M HCl pH 1.2 in the presence of isoniazid gastric-resistant sustained-release microspheres was only 4.44%. These results indicate that the degradation of rifampicin in the presence of isoniazid in acidic media can be reduced by encapsulation of both active pharmaceutical ingredients to ensure release in different segments of the gastrointestinal tract, potentially improving the bioavailability of rifampicin.